Lactobacillus rhamnosus GG powder supplementation alleviates intestinal injury in piglets challenged by porcine epidemic diarrhea virus - Zhaoyang Xu; Qian Zhang; Mengjun Wu; Yanyan Zhang; Zhonghua Li; Hanxiao Li; Chenmin Yu; Xiaohan Zhang; Di Zhao; Lei Wang; Yongqing Hou; Tao Wu (Frontiers in Cellular and Infection Microbiology, 2024)
Porcine epidemic diarrhea virus (PEDV) has become a challenging problem in pig industry worldwide, causing significant profit losses. Lactobacillus rhamnosus GG (LGG) has been regarded as a safe probiotic strain and has been shown to exert protective effects on the intestinal dysfunction caused by PEDV. This study evaluated the effect of LGG on the gut health of lactating piglets challenged with PEDV. Fifteen piglets at 7 days of age were equally assigned into 3 groups (5 piglets per group): 1) control group (basal diet); 2) PEDV group: (basal diet + PEDV challenged); 3) LGG + PEDV group (basal diet + 3×109 CFU/pig/day LGG + PEDV). The trial lasted 11 days including 3 days of adaptation. The treatment with LGG was from D4 to D10. PEDV challenge was carried out on D8. PEDV infection disrupted the cell structure, undermined the integrity of the intestinal tract, and induced oxidative stress, and intestinal damage of piglets. Supplementation of LGG improved intestinal morphology, enhanced intestinal antioxidant capacity, and alleviated jejunal mucosal inflammation and lipid metabolism disorders in PEDV-infected piglets, which may be regulated by LGG by altering the expression of TNF signaling pathway, PPAR signaling pathway, and fat digestion and absorption pathway.